The Therapeutic Applications Of Aptamers And Aptamer-Conjugated Nanoparticles In Cancer, Inflammatory And Viral Diseases (Journal of Pharmaceutical Negative Results, 2022)
Health care modalities that are more predictable and effective are the result of advances in early diagnosis and precise treatment options. Aptamers are three-dimensional structures made of nucleic acids that selectively bind to a target site. In the creation of aptamer-based drug delivery systems, the physicochemical properties of aptamers, their conjugation with nanoparticles (NPs) in theranostics, and their internalization have been found to be of interest.As a result, our goal was to provide an overview of the structure and production of aptamers, followed by the benefits of aptamer-conjugated nanoparticles and their applications as theranostics in oncology, inflammatory, and viral diseases. After that, a number of reports on aptamer internalization strategies, the efficiency of aptamers in comparison to their analogs, and the implications of aptamers for clinical trials were discussed. Last but not least, we talked about the problems that actively targeted aptamers face right now and what the future holds for their use in medicine. In conclusion, aptamer-based therapeutic platform development in clinical trials may benefit greatly from this review.